Strategies to Increase Financial Planning Literacy in Life Insurance at PT Pancaran Kemilau Sejahtera (PaninDai-ichiLife) - Simamora, David Rivano; Sishadiyati, Sishadiyati; Primandhana, Wiwin Priana (Pascasarjana Universitas Mataram, 2025)
The influence of someone's interest in using Life Insurance as their strategy in financial planning. Through this writing, it shows that a person has pros and cons in using life insurance. The quality of products and services, the skill and appeal of insurance agents in describing the advantages of their products, and the degree of money a person has directly affects their capacity to afford insurance products are all factors that affect their use of life insurance. The results show that the level of service of the insurance product, as well as the attractiveness of the agent, are things that influence a potential customer to want to use a Life Insurance product. By doing this, it is believed that one can gain a better grasp of financial planning and be able to develop strategies for it.